PELATIHAN PENYUSUNAN MEDIA PEMBELAJARAN BAGI MAHASISWA PENDIDIKAN JASMANI, KESEHATAN, DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN UNIVERSITAS NEGERI MAKASSAR - Irvan Sir; Sarifin G.; Sufitriyono Sufitriyono; Agus Sutriawan (KORSAcs: Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service aims to provide training to students of physical education, health and recreation regarding the use of Canva media as a tool for compiling teaching materials. This activity is carried out by providing knowledge in making presentation media, posters or logos for lecture purposes that can be used for free through Canva. Based on the results of observations, it was found that students in the Physical Education, Health, and Recreation Study Program did not yet have the knowledge and skills in making interesting and innovative teaching materials. The methods used in this service activity are the presentation method, lectures, and direct practice in using Canva. The number of participants, as many as 115 students from the class of 2022, came from the Physical Education, Health, and Recreation study programs, Faculty of Sports Science, Makassar State University. The results of the service show that students' skills and knowledge are increasing in making interesting teaching materials through Canva media.